Pengaruh Investment Opportunity Set, Free Cash Flow dan Debt to Equity Ratio terhadap Nilai Perusahaan - Lusiana; Indriyenni; Hilda Mary (Universitas Putra Indonesia YPTK Padang, 2019)
The study aimed was to analyze the effect of Investment Opportunity Set, Free Cash Flow, and Debt to Equity Ratio as partially and simultaneously on Firm Value. The data used are secondary data in the form of financial reports and annual reports from 2013 to 2017. Sample research method used in this research is purposive sampiling and statistical test used to test the hypothesis is by using multiple regression analysis. The results of the study indicate that investment opporuntiy set has a positive and significant effect on firm value, free cash flow has a positive and significant effect on firm value, and debt to equity ratio insignificant to firm value, investment opportunity set, free cash flow, and debt to equity ratio together affect the firm value.